Palliative Tumor Control by Trabectedin in Pediatric Advanced Sarcoma - Nasser, Soumana C. (2011)
Refractory soft tissue sarcomas carry a poor prognosis and limited treatment options require the use of new chemotherapeutic agents. We report the case of an eight year old boy with non metastatic alveolar rhabdomyosarcoma of the right forearm (Group 3, Stage III). After treatment failure of several chemotherapeutic regimens and progression of his disease, Trabectedin was administered at 1.3 mg/m2/dose intravenously over 24 hours for two cycles. The patient's quality of life improved as noted by a significant decrease in opiate requirements and ability to tolerate oral intake. The drug was well tolerated with the exception of transient neutropenia.